Diseño e Implementación de un Prototipo Basado en IoT para el Monitoreo de los Parámetros Básicos de la Calidad del Agua en la Planta Potabilizadora del Sector de Pucará - Jimbo Sarmiento, Edwin Abel (2023)
The quality of water is one of the most important issues today because it is the vital liquid for human beings, and also because its qualities are being affected by pollution. National and international organizations seek to improve quality through different methods, for example, reducing pollution, protecting green areas or improving control of water sanitation in drinking water treatment plants. The present work is related to the control of water quality in treatment plants, through the use of updated methods. With the above, an IoT-based prototype was implemented at the Pucará water treatment plant in the canton of Loja for monitoring the 4 basic parameters of water quality using the low-power wireless network called LoRaWAN. To achieve this result, a design process was carried out where the use of the RadioPlanner software for the simulation of the coverage diagram stands out. Likewise, 4 sensors were used to collect the information on an Arduino Uno board, the same one that transmits the information by UART serial communication to the Tx TTGO V1 board. Also, the "TTN" network server was used, which communicates with the Tx TTGO V1 board through the low-power LoRaWAN network, and for this the HT-M00 gateway was used. Finally, in the "TagoIO" application server, a monitoring panel was developed with the data from the "TTN" network server. As general results, with the IoT monitoring system it was possible to collect a large amount of information in a simple and comfortable way. Keywords: water quality, LoRaWAN, Arduino IDE, network server, application server, sensors.